2022
DOI: 10.32677/yjm.v1i1.3292
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D deficiency with dyslipidemia, glycemic control and microalbuminuria in patients with type 2 Diabetes mellitus in Qatar

Abstract: Background: Type 2 diabetes mellitus has been found to be associated with 25(OH)D (vitamin D) deficiency. The aim of this study was to the prevalence of vitamin D deficiency in T2DM patients in Qatar and the correlation between vitamin D deficiency and other variables such as dyslipidemia and glycemic control and microalbuminuria. Methods: This retrospective cross-sectional analytical study was carried out at the Hamad General Hospital medical outpatient clinic, in which adult patients (? 18 years) with type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another study in Pakistan has recorded a little lower incidence of VD deficiency in patients with T2DM (41.50%) [ 10 ]. Various studies around the globe have reported a prevalence of VD deficiency in patients with T2DM that ranges from 29.50% to 91% [ 6 , 11 ]. The large range of the prevalence of VD deficiency in T2DM patients could be due to several factors like geographical, racial, dietary, and most importantly the stage of T2DM in patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study in Pakistan has recorded a little lower incidence of VD deficiency in patients with T2DM (41.50%) [ 10 ]. Various studies around the globe have reported a prevalence of VD deficiency in patients with T2DM that ranges from 29.50% to 91% [ 6 , 11 ]. The large range of the prevalence of VD deficiency in T2DM patients could be due to several factors like geographical, racial, dietary, and most importantly the stage of T2DM in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VD deficiency also causes insulin insensitivity [ 4 , 12 ]. Whereas, adequate replacement of VD not only improves the blood glucose level via controlling the insulin signaling but also protects against cardiovascular diseases, autoimmune diseases, infectious diseases, and musculoskeletal disorders by regulating lipogenesis and inflammation [ 4 , 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a secondary post hoc analysis of collected data from our previous study titled "Association of Vitamin D deficiency with dyslipidemia, glycemic control, and microalbuminuria in patients with T2DM in Qatar" [7], which was conducted from January 1, to July 31, 2018. The collected data were used to conduct a new study with modified objectives, without using patients' medical records.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%